Coldpack Intervention to Alleviate Hematoma in Post-Percutaneous Coronary Intervention Patient: A Case Study - Suhanda Suhanda; Silvia Yulisti Susanto Putri; Henri Setiawan (Inspirasi Foundation, 2023)
Introduction: Interventions necessary for patients experiencing Coronary Artery Disease (CAD) include revascularization through Coronary Artery Bypass or Percutaneous Coronary Intervention (PCI). Vascular complications resulting from PCI procedures include hematoma, microvascular aneurysm, bleeding, edema, incision site pain, ecchymosis, embolism, arterial occlusion, arterial spasm, arteriovenous fistula, and retroperitoneal hematoma. Objective: To describe the nursing intervention outcomes using cold packs to address hematoma in post-PCI patients with femoral sheath access. Method: A qualitative study employing a case study approach conducted from March 23-25, 2023, at the Heart and Vascular Hospital Tasikmalaya. Inclusion criteria for participants include a diagnosis of Coronary Artery Disease (CAD), prior PCI intervention, PCI access via femoral sheath, and willingness to provide informed consent. The intervention involves the application of a cold pack. Research instruments utilized in this study include semi-structured interviews (in-depth interviews) and observations using The Femoral Scale. Result: The use of cold packs to address hematoma in post-PCI patients with femoral sheath access is effective. This is evidenced by the absence of hematoma in post-PCI patients with femoral access after applying mechanical pressure with a cold pack. During the observation, patients did not express significant complaints; they reported greater comfort using a cold pack compared to the conventional sandbag approach. Conclusion: The utilization of cold packs in this case can be considered an alternative to sandbags to enhance patient comfort. However, it is imperative to conduct additional monitoring when removing the cold pack, especially during the 6-hour immobilization period, to ensure patient awareness and compliance with immobilization protocols.